Characterization of Anopheles gambiae D7 salivary proteins as markers of human-mosquito bite contact - Oseno, Brenda; Marura, Faith; Ogwang, Rodney; Muturi, Martha; Njunge, James; Nkumama, Irene Nailain; Mwakesi, Robert; Mwai, Kennedy; Rono, Martin K.; Mwakubambanya, Ramadhan; Osier, Faith; Tuju, James (Parasites & vectors, 2022)
Malaria is transmitted when infected Anopheles mosquitoes take a blood meal. During this process, the mosquitoes inject a cocktail of bioactive proteins that elicit antibody responses in humans and could be used as biomarkers of exposure to mosquito bites. This study evaluated the utility of IgG responses to members of the Anopheles gambiae D7 protein family as serological markers of human-vector contact.
Gesehen am 30.09.2022